Removal of carbonate ion through cellulose fiber supported solid membrane - Gaikwad, Abaji G. (Journal of Engineered Fibers and Fabrics, 2014)
A novel fiber supported solid membrane was prepared by chemical modification of cellulose fiber with tartaric acid, 8-hydroxyquinoline and magnesium carbonate for removal of bicarbonate ion. Loading effect of tartaric acid, magnesium metal ion and 8-hydroxyquinoline over cellulose fiber was studied for removal of carbonate ion. The selective removal of carbonate, sulfate, phosphate, and nitrate ions through fiber supported solid membrane was investigated. The removal of carbonate ion with/without bubbling of CO2 was determined in source and receiving phases.